Analysis of Quality of Service for the AOMDV Routing Protocol - V. B. Kute (Engineering, Technology & Applied Science Research, 2013)
Due to the dynamic nature of Mobile Ad-hoc Networks (MANETs), the provision of Quality of Service (QoS) guarantees is challenging. The route failure probability in a MANET is increased due to the mobility of nodes, which increases routing overhead. Multi-path routing protocols have relatively greater ability to reduce the routing overheads. This paper discuses the performance analysis of the Ad-hoc On-Demand Multi-Path Distance Vector (AOMDV) routing protocol. AOMDV is a multi-path extension of a very well known single path routing protocol, (AODV). Extensive simulations were carried out using ns-2.34 and the study concluded that for CBR traffic AOMDV performance degrades as the data packet generation rate increases.